2010
DOI: 10.1073/pnas.1015340107
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of glass-forming liquids suggest that dynamic crossover temperature is as important as the glass transition temperature

Abstract: It is becoming common practice to partition glass-forming liquids into two classes based on the dependence of the shear viscosity η on temperature T . In an Arrhenius plot, ln η vs 1∕T , a strong liquid shows linear behavior whereas a fragile liquid exhibits an upward curvature [super-Arrhenius (SA) behavior], a situation customarily described by using the Vogel-Fulcher-Tammann law. Here we analyze existing data of the transport coefficients of 84 glassforming liquids. We show the data are consistent, on decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
238
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(260 citation statements)
references
References 47 publications
22
238
0
Order By: Relevance
“…MDS of another water model (mW) find a crossover from ζ = −1 to ζ = −0.75 (62). The overall picture is that a similar crossover in the FSE exponent is observed for real water, simulations of water models (37,38,62), and experiments on ortho-terphenyl (23,24), Tris-naphthylbenzene (27), and seven other liquids (58). In the case of rotation, we find that FSED experimentally holds with a single exponent ζ = 0.97 over more than 2 decades.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…MDS of another water model (mW) find a crossover from ζ = −1 to ζ = −0.75 (62). The overall picture is that a similar crossover in the FSE exponent is observed for real water, simulations of water models (37,38,62), and experiments on ortho-terphenyl (23,24), Tris-naphthylbenzene (27), and seven other liquids (58). In the case of rotation, we find that FSED experimentally holds with a single exponent ζ = 0.97 over more than 2 decades.…”
Section: Resultssupporting
confidence: 48%
“…The FSE relation has since been tested for a variety of liquids and found to give a good description far from the glass transition (57). A putative universal crossover from FSE with ζ = −1 to ζ ' −0.85 upon cooling was suggested by the analysis of data for nine liquids (58). Simulations of models of supercooled fragile liquids (East models) find ζ ' −0.7 to −0.8 (59,60).…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is seen in the physical properties of all glass-forming systems (and supercooled liquids)-structural relaxation allows a transition from the viscous to the elastic regime. It was recently shown that structural relaxation causes the transport properties of all supercooled liquids to be characterized by a dynamic crossover from super-Arrhenius to Arrhenius behavior (41). Using mode coupling to examine the hopping processes among these relaxing structures (39) we find the crossover temperature of the transition from liquidlike to solidlike behavior toward dynamic arrest (or glass transition).…”
Section: Methodsmentioning
confidence: 99%
“…The temperature associated with this overlap separates the lowtemperature Arrhenius behavior, typical for a glass, from the high-temperature super-exponential behavior, typical for a supercooled liquid. Both are separated by the crossover temperature * that unlike the glass transition temperature does not depend on the cooling rate 37,38 . In literature, this transition is sometimes referred to as fragile-to-strong (FTS) transition upon cooling 39 .…”
Section: Figmentioning
confidence: 99%